2020
DOI: 10.1029/2020tc006071
|View full text |Cite
|
Sign up to set email alerts
|

Provenance Record of Late Mesoproterozoic to Early Neoproterozoic Units, West Hainan, South China, and Implications for Rodinia Reconstruction

Abstract: Unraveling the character and source of late Mesoproterozoic‐early Neoproterozoic sedimentary sequences is crucial in constraining Rodinia reconstructions. We carried out an integrated geochemical, zircon U‐Pb geochronological and Lu‐Hf isotopic study of the Shilu Group and the overlying Shihuiding Formation in Hainan, South China. These two successions are chemically mature and dominated by siliceous components. The Shilu Group was mainly derived from felsic arc lithologies whereas the Shihuiding Formation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 118 publications
(245 reference statements)
0
15
0
Order By: Relevance
“…Metamorphic zircons of 1300-1000 Ma are widely exposed in the metasedimentary rocks, gneisses, and magmatic rocks of the Baoban Complex but are largely absent within the Shilu Group (layers 3-6) [37-39,70,77] (Figure 2), which indicates that these sedimentary and magmatic rocks experienced metamorphism during 1300-1000 Ma. Abundant detrital zircon U-Pb data for layers 3-6 of the Shilu Group constrain the maximum depositional age of the mid-upper Shilu Group to approximately 1100 Ma [60,70,71]. All of these results support that the mid-upper Shilu Group is a depositional system distinctively different from the metasedimentary rocks in the Baoban Complex.…”
Section: Tectonostratigraphic Relationships Between the Baoban Comple...mentioning
confidence: 66%
See 3 more Smart Citations
“…Metamorphic zircons of 1300-1000 Ma are widely exposed in the metasedimentary rocks, gneisses, and magmatic rocks of the Baoban Complex but are largely absent within the Shilu Group (layers 3-6) [37-39,70,77] (Figure 2), which indicates that these sedimentary and magmatic rocks experienced metamorphism during 1300-1000 Ma. Abundant detrital zircon U-Pb data for layers 3-6 of the Shilu Group constrain the maximum depositional age of the mid-upper Shilu Group to approximately 1100 Ma [60,70,71]. All of these results support that the mid-upper Shilu Group is a depositional system distinctively different from the metasedimentary rocks in the Baoban Complex.…”
Section: Tectonostratigraphic Relationships Between the Baoban Comple...mentioning
confidence: 66%
“…It can be seen that the disagreement mainly focuses on the age of each component unit of the "Baoban Group" and the relationship between them. With the continuous improvement of analytical methods and in-depth research, an increasing number of researchers have gradually realized that the "Baoban Group" mainly consists of supracrustal rocks and later intruded granitic and metamafic rocks and named it the "Baoban Complex" [37][38][39]52,60,70,71]. The supracrustal rocks are divided from bottom to top into the Gezhencun and Ewenling formations, and they were intruded by gneissic granitoids and amphibolites.…”
Section: Geological Setting and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the complex magmatic During the Mesoproterozoic-Neoproterozoic Grenvillian Orogeny (1.3-0.9 Ga), the residual fragments of the Columbia supercontinent that were not completely disintegrated converged to form the Rodinia supercontinent (Fig. 7b) (Cawood, 2020;Zhang et al 2020b;Wu et al 2023). The Grenvillian Orogeny (1.3-0.9 Ga) is extensively recorded in both Laurentia and Gondwana (Fig.…”
Section: B Sediment Sourcesmentioning
confidence: 91%